Identity and Identity Politics in Nigeria: A Reflection on the Indicators - Tope Shola Akinyetun (Društvene i Humanističke Studije, 2021)
Nigeria is a nation with plural ethnic, religious, lingual and cultural identities that are constantlyexploited by the political class to promote their selfish interest. Although not a determinant forconflict, diversity in Nigeria has unjustifiably sparked identity-based conflicts which necessitateseparatism, insurgency and ethnic restiveness – among others, which threatens to drive thecountry to a perpetual state of fragility. This paper thence sought to assess Nigeria’s tortuousexperience with identity and identity politics with particular reference to ethnic, religious andlingual challenges. The paper furthers the discussion on identity politics in Nigeria to profferpracticable solutions. It argues that identity consciousness has overtaken national consciousnessand engendered a relationship characterized by domination, superiority and hegemony by thevarious groups. It reveals that the currency of politics is an ethnic-hegemony-rivalry sentimentthat threatens national integration. The paper reviews available literature on the subject matterfrom peer-reviewed journal articles, reports of reputable international organizations, workingpapers and newspaper articles. It concluded that identities have become powerful manipulativeinstruments in the hands of the political elites used to divide the Nigerian populace. Itrecommended the promotion of justice, equity and fairness in governance to ameliorate thechances of identity dissension and identity-based conflicts.